An outbreak of human Rhinovirus-A21 infection in a psychiatric ward during COVID-19 pandemic - Chen, Lung-Chiung; Chiu, Chih-Chien; Chang, Fu-Mei; Wu, Pei-Yuan; Yang, Shu-Li; Huang, Chung-Guei; Huang, Yhu-Chering (Journal of microbiology, immunology and infection, 2022)
A cluster of acute respiratory illnesses involving 12 inpatients and 3 healthcare workers occurred in a psychiatric ward. Eight of them were identified as HRV-A21. Fever and cough were the most common symptoms. The study also provides further evidence of the impact of HRV on lower respiratory tract illness.